Type I and II interferons, transcription factors and major histocompatibility complexes were enhanced by knocking down the PRRSV-induced transforming growth factor beta in monocytes co-cultured with peripheral blood lymphocytes - Fabros, Dante; Charerntantanakul, Wasin (Frontiers in Immunology, 2024)
The innate and adaptive immune responses elicited by porcine reproductive and respiratory syndrome virus (PRRSV) infection are known to be poor. This study investigates the impact of PRRSV-induced transforming growth factor beta 1 (TGFβ1) on the expressions of type I and II interferons (IFNs), transcription factors, major histocompatibility complexes (MHC), anti-inflammatory and pro-inflammatory cytokines in PRRSV-infected co-cultures of monocytes and peripheral blood lymphocytes (PBL). Phosphorothioate-modified antisense oligodeoxynucleotide (AS ODN) specific to the AUG region of porcine TGFβ1 mRNA was synthesized and successfully knocked down TGFβ1 mRNA expression and protein translation. Monocytes transfected with TGFβAS1 ODN, then simultaneously co-cultured with PBL and inoculated with either classical PRRSV-2 (cPRRSV-2) or highly pathogenic PRRSV-2 (HP-PRRSV-2) showed a significant reduction in TGFβ1 mRNA expression and a significant increase in the mRNA expressions of IFNα, IFNγ, MHC-I, MHC-II, signal transducer and activator of transcription 1 (STAT1), and STAT2. Additionally, transfection of TGFβAS1 ODN in the monocyte and PBL co-culture inoculated with cPRRSV-2 significantly increased the mRNA expression of interleukin-12p40 (IL-12p40). PRRSV-2 RNA copy numbers were significantly reduced in monocytes and PBL co-culture transfected with TGFβAS1 ODN compared to the untransfected control. The yields of PRRSV-2 RNA copy numbers in PRRSV-2-inoculated monocytes and PBL co-culture were sustained and reduced by porcine TGFβ1 (rTGFβ1) and recombinant porcine IFNα (rIFNα), respectively. These findings highlight the strategy employed by PRRSV to suppress the innate immune response through the induction of TGFβ expression. The inclusion of TGFβ as a parameter for future PRRSV vaccine and vaccine adjuvant candidates is recommended.